Morbidity and mortality pattern of very low birth weight infants admitted in SNCU in a South Asian tertiary care centre - S., Kabilan; Kumar, Mekalai Suresh (International Journal of Contemporary Pediatrics, 2018)
Background: Around 4-8% of all live births are very low birth weight (VLBW) infants. In India currently 8 million VLBW infants are born each year which constitutes 40% of global burden the highest for any country. The present study was done to determine frequency of disease, complications, survival rate and risk factors for morbidity and mortality in VLBW babies. Methods: Between October 2016 and September 2017, we did a cross-sectional retrospective study at level three SNCU with >98% inborn admissions and about more than 10000 deliveries per year. The American Academy of Pediatrics protocol for neonatal resuscitation was followed for the management of VLBW. Data were entered in predetermined proforma and statistical analysis was done. Results: There were 154 registered cases of VLBW [75 females (48.7%) and 79 males (51.3%)]. The mean birth weight=1.198 (SD=0.211). The mean gestational age in weeks was 31.9 (SD=3.095). Majority of them were in the gestational age 33-36 weeks (n=68, 44.2%), small for gestational age (n=89, 57.8), delivered through normal vaginal delivery (n=95, 61.7%), singletons (n=126, 81.8%), inborn (n=152, 98.7%), maternal age between 21-30 (n=95, 61.6%), clear amniotic fluid (n=137, 89%), on antenatal steroids (n=59, 38.3%), maternal disease were present in 55 mothers (33%) and gestational hypertension being more common (n=14, 9.6%). Majority of babies had Respiratory Distress Syndrome (n=56, 33.6%), birth asphyxia (n=54 32.4%) and sepsis (n=46, 27.6%). Mortality of 40.3% (n=62) observed in present study. Forty three babies with RDS, twenty babies with asphyxia and eight babies with sepsis expired. Conclusions: Multiple regression analysis with adjusted estimates of odds ratio showed that very low birth weight, low Apgar score at 5 minute, intubation and mechanical ventilation were predictors of outcome of VLBW babies. Birth weight and mechanical ventilation were significant predictors of the outcome of ELBW babies.